NATURE AND CHARACTERISTICS OF LABOR DISCRIMINATION: A COMPREHENSIVE ANALYSIS - Tursunmurodov Komron Turgun ogli (Scholar Express Journals, 2025)
This paper discusses the problems of discrimination in labor relations and reveals their essence and features. The purpose of this article is to protect employees from discriminatory acts of employers, to increase legal awareness, legal culture of employees and employers, as well as to prevent violations of the rights, freedoms and legitimate interests of citizens in the field of labor. The author underlines the urgency to fight gender discrimination, explaining the essence of this phenomenon in life situations. Also, all necessary regulatory legal acts were applied in the work to protect the rights of employees and to prevent discrimination in the field of labor
Keywords: Discrimination at work; gender discrimination; discriminatory act